Doppler Spectrum Analysis in Three-Dimensional 5G Millimeter-Wave Channel Models - Cerezo-Barranco, Antonio; Ruiz-Vega, Fernando Jesús; Aguayo-Torres, María del Carmen (My University, 2019)
This article is contextualized in the mobile communications systems where there are multiple factors to consider: mobility, frequency, obstacles, reflectors, etc. In this paper, is presented an evaluation of the Doppler spectrum in a Three-Dimensional (3D) channel model for different frequencies, User Terminal (UT) directions and UT speeds. To commence, it introduces the channel model that is used for the simulations, then the Classical Doppler Spectrum frequently used in Two-Dimensional (2D) channel models is entered. Finally, it tries the Doppler Spectrum for the some typical 5G frequencies, speeds up to 500 km/h and for the motion direction in the 3D space.
Keywords: Comunicaciones; Telecomunicaciones; 5G; Three-dimensional; Millimeter-wave; Channel models; Mobile communications system; Doppler spectrum; Radio-propagation model; Transmitter; Receiver; Cluster; Ray; Signal